Mitigation, adaptation, suffering : in search of the right mix in the face of climate change - Henry Tulkens; Vincent van Steenberghe (Center for Economic Studies and ifo Institute (CESifo), 2009)
The usually assumed two categories of costs involved in climate change policy analysis, namely abatement and damage costs, hide the presence of a third category, namely adaptation costs. This dodges the determination of an appropriate level for them. Including adaptation costs explicitly in the total environmental cost function allows one to characterize the optimal (cost minimizing) balance between the three categories, in statics as well as in dynamics. Implications are derived for cost benefit analysis of adaptation expenditures.
Keywords: Q54; Q58; 330; Klimaschutz; Policy-Mix; Umweltschutzkosten; Anpassungskosten; Kosten-Nutzen-Analyse; Theorie